The impact of a preventive promotional program on the protective factors of suicide risk among adolescents of Application UNHEVAL National School - Sánchez Infantas, Rosario (2017)
This investigation was done in order to identify students with low levels of protective factors in suicidal risk (assertiveness, effective communication, self-esteem, decision making), evaluated with a questionnaire Ad Hoc (authors) and complementary the suicide risk, assessed with the Suicide Risk Questionnaire of Plutchik, in130 students of second, third and fourth year of a State School in the town of Huánuco, Peru. 29% (38 students) fulfill the inclusion criteria mentioned. We prepared and implemented a program to increase the protective factors mentioned and have an indirect influence on the suicide risk or other problems associated with unsatisfied needs found. Using One-Group Pretest-Posttest Design, the effect of the program (8 sessions with students and one with the staff of the school) was evaluated in 25 students who attended all workshops. Significant differences between the two assessments, for each one of the factors and the total score by Test-T, are found, with a p-value of 0.05.